PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PT. ADIRA DINAMIKA MULTI FINANCE Tbk. CABANG PONDOK GEDE - Nira Marlianda Sentosa; M. Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The purpose of the research service quality and customer satisfaction on customer loyalty at PT. Adira Dinamika Multi Finance Tbk Pondok Gede Branch. In this study used 114 sample respondents. Data analysis method used with simultaneous and partial linear regression analysis techniques and simple linear regression. The results of the study concluded that there is a significant influence of service quality and customer satisfaction on customer loyalty at PT. Adira Dinamika Multi Finance Tbk, either simultaneous or partial.